Whistle-blowing Intention: The Effects of Moral Intensity, Organizational and Professional Commitment - Aditya Pandu Wicaksono, Dekar Urumsah, Briyan Efflin Syahputra, (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
This research aimed to investigate the effects of moral intensity, organizational and professional commitment on whistle-blowing intention. This research employed quantitive approach using survey method by distributing questionnaries to the participants. The participants were government employees working in the province of DIY (Daerah Istimewa Yogyakarta), Indonesia. The total number of the respondents in this research was 160. The statistical test in this research was assisted with smartPLS. This research result has found that moral intensity and professional commitment significantly gave positive influence on whistle-blowing intention. However, organization commitment did not significantly influence the whistle-blowing intention.